An analytic model for selection of and allocation among third party logistics service providers. (5th April 2010) - Rajesh, R.; Pugazhendhi, S.; Ganesh, K.
Third party logistics service provider (3PLSP) selection is a multi-criteria decision-making (MCDM) problem in a supply chain involving many qualitative and quantitative factors. The selection of an efficient and potential set of 3PLSPs that can meet the particular requirements of the customer and with whom the customer can strengthen its relationships is a crucial decision. This decision is influenced by several factors often in conflict, such as price, services offered, location, technology, quality, etc., and the problem complexity increases because of the imprecision and uncertainty involved in the decision-making process. In this paper a simple but effective approach to handle this kind of problems is proposed and the problem of allocation of workloads among the ranked 3PLSPs satisfying the set of constraints and meeting the set objective is also addressed. The application of the proposed approach to a real case is also presented.